Nutritional Status of Preschool Children Infected With Giardia Intestinalis - SM Sadjjadi; N Tanideh (Tehran University of Medical Sciences, 2005)
Giardia intestinalis is the most common intestinal parasite in human worldwide. It can produce a wide spectrum of clinical manifestations. In order to assess the nutritional status of preschool children infected with Giardia intestinalis, a cross sectional study was made in Marvdasht city, Fars Province, Southern Iran. A total of 337 preschool boys and girls aged 3-6 years were randomly selected for stool examination of intestinal parasites as well as measurement of height, weight, head and arm circumferences. A total of 77 individuals were infected with G. intestinalis. Seventy-one individuals who had only G. intestinalis and 229 with no parasitic infections were selected as infected and control groups, respectively. Z-Score of -2SD was used as cut off point of malnutrition. A total of 9 (12.7%) of infected children and 18 (7.9%) of non infected individuals had a height for age Z-score (HAZ) below -2SD. Eight (11.3%) of former group had a weight for age Z-score (WAZ) under-2SD. In control group 4.4% of preschool children had WAZ under-2SD. 4.2% of infected children had a weight for height Z-score (WHZ) under-2SD but none of the controls had it. Statistical analysis showed a significant difference in height, weight, head circumference, HAZ, and WAZ between infected and control children (P